Nano-porous carbon coated SiC whisker modified AgCuTi brazing filler metal as well as preparation method and application thereof
Through the nano -porous carbon covering treatment of SIC crystal, and mix with Agcuti powder to form a modified raw material, solve the problem of excessive reaction of nano -composite rafters at the welding temperature, improve the shear strength of the joints of the joint. And enhance the mechanical properties of the phase.
Patent Information
- Application Number
- CN202411477693.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing nanocomposite AgCuTi brazing is prone to overreact with the active brazing material at the brazing temperature, which makes it difficult to fully exert the mechanical properties of the enhanced phase, and the large-size brittle phases inside the weld are distributed more, affecting the shear strength of the joint.
Through the SIC crystal must be used for nano -porous carbon coverage, it is mixed with AGCUTI powder to form a nano -porous carbon coating SIC crystal modified AGCUTI turtle material. This method avoids the direct contact between SIC crystal whispering with the active pyramid through the cover of porous carbon, which reduces excessive reactions and optimizes the distribution of enhanced phases.
It effectively avoids the excessive reaction between the nano-reinforcement phase and the active solder, reduces the distribution of large-sized brittle phases inside the weld, improves the shear strength of the joint, and maximizes the mechanical properties of the reinforcement phase.
Smart Images

Figure CN119347209A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of brazing connection, and in particular relates to a nano porous carbon coated SiC whisker modified AgCuTi brazing material and a preparation method and application thereof. Background Art
[0002] AgCuTi solder is a widely used active solder. Since the active element Ti can react with most ceramics and C / C composites to wet the surface of the base material, AgCuTi active solder is widely used for brazing connections between dissimilar materials such as metals, ceramics, and C / C composites. However, the coefficient of thermal expansion (CTE) between AgCuTi solder and C / C and ceramics is significantly different, resulting in high residual thermal stress at the joint. In order to further eliminate the influence of thermal stress, many related research works in recent years have shown that the negative impact of thermal stress on the joint can be improved by adding a plastic metal interlayer or adding a low CTE reinforcing phase to the solder, thereby improving its performance.
[0003] Reference 1 "In-Situ synthesized TiC nano-flakes reinforced C / C composite-Nbbrazed joint[J]. Journal of the European Ceramic Society, 2018, 38(4): 1059-1068" uses a polymer carbonization process to obtain a carbon-coated Cu foam composite interlayer, which is assembled with AgCuTi foil and brazed with C / C composite and Nb. The carbon layer coated on the Cu foam reacts with the Ti element to form uniformly distributed in-situ TiC nanoflakes in the joint. However, the current research on carbon-based reinforced metal foam materials (Reference 2 A novel in-situforming 3D core-sheath interlayer designed to strengthen C f / C composite-Nbjoints during brazing[J]. Materials Characterization, 2024, 208: 113661) showed that due to the large difference in CTE between the carbon and metal foam matrix, the mechanical properties of the network structure are unstable, reducing the strain adjustment ability of the complete grid structure. Another commonly used method is to add micro-nano scale reinforcement phases to the brazing filler metal, for example, adding micron-scale SiC particles to AgCuTi brazing filler metal, and studying the effect of the volume percentage of reinforcement particles on the brazing joint structure (Reference 3 "Joining of C / C composite to TC4 using SiC particle-reinforced brazing alloy[J]Materials Characterization, 2010, 61(6): 635-639"). The results show that the addition of SiC particles can reduce the thermal expansion coefficient of the brazing alloy, thereby reducing the residual stress of the C / C-metal joint, but a large amount of SiC particles (volume percentage ~35 vol.%) consume excessive Ti elements in the brazing filler metal, agglomerate and form defects such as pores. SiC ceramics were brazed by adding a brazing material composed of graphene nanoplatelets (GNPs) to the AgCuTi brazing filler (Reference 4 “Graphene nanoplatelets reinforced AgCuTi composite filler for brazing SiCceramic[J] Journal of the European Ceramic Society, 2019, 39: 696–704.”). The TiC particles synthesized by the in-situ reaction of Ti and GNPs promoted the heterogeneous nucleation of TiCu and Cu(s,s), but the reinforcing phase GNPs reacted with the Ti element in large quantities, weakening its reinforcement effect, so that the shear strength of the joint only reached 38 MPa.
[0004] Micro-nano scale reinforcement phases (micro-nano ceramic particles, nanocarbon, etc.) are widely used in the modification of AgCuTi solder. However, most reinforcement phases can react with the active Ti element in the solder at the brazing temperature, making it difficult to fully exert their strengthening effect. Excessive consumption of the Ti element reduces the thickness of the reaction layer with the base material. The reaction activity of the reinforcement phase and the solder can be reduced by carbonizing the precursor or coating the carbon layer, but the formed annular carbon layer structure is prone to form aggregated brittle products after brazing; in addition, the influence range of the reinforcement phase and the carbon layer is limited, and it is difficult to inhibit the formation of large-sized brittle phases in the brazing layer in a larger space. Therefore, how to reduce the distribution of large-sized brittle phases inside the weld while effectively avoiding excessive reaction of the nano-reinforced phase with the active solder at the brazing temperature is an urgent problem to be solved. Summary of the invention
[0005] The purpose of the present invention is to provide a nanoporous carbon coated SiC whisker modified AgCuTi solder and its preparation method and application, so as to solve the technical problem that the nano-reinforcement phase used in the existing nano-composite AgCuTi solder modification method is prone to excessive reaction with the active solder.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder, comprising the following steps: The SiC whiskers are subjected to chemical vapor deposition treatment to obtain nanoporous carbon-coated SiC whiskers; The nanoporous carbon-coated SiC whisker and AgCuTi powder are mixed and added into a solvent for stirring. The powder is collected and ground to obtain the nanoporous carbon-coated SiC whisker modified AgCuTi solder.
[0007] Furthermore, the chemical vapor deposition process uses methanol as a precursor and is deposited at 1140-1170° C. for 2-4 hours.
[0008] Furthermore, the usage ratio of the nanoporous carbon-coated SiC whisker, AgCuTi powder and solvent is (0.0125 g-0.05) g: (4.9875-4.975) g: 30 mL.
[0009] Further, the solvent is ethanol; The stirring is magnetic stirring; the temperature of the magnetic stirring is 75-85°C.
[0010] Furthermore, the grinding time is 30 to 60 minutes.
[0011] The invention also discloses a nano porous carbon coated SiC whisker modified AgCuTi solder prepared by the preparation method.
[0012] The invention also discloses the application of the nanoporous carbon coated SiC whisker modified AgCuTi solder, and the application of the nanoporous carbon coated SiC whisker modified AgCuTi solder in brazing C / C-Cu joints.
[0013] Furthermore, when the nanoporous carbon-coated SiC whisker-modified AgCuTi solder is used in brazing a C / C-Cu joint, the following steps are included: The nanoporous carbon-coated SiC whisker-modified AgCuTi solder and a binder are mixed to obtain a mixed slurry; The C / C and Cu are pretreated, and then the mixed slurry is applied to the surfaces of the C / C and Cu to be connected, and then they are bonded to form a sandwich-type prefabricated structure; The obtained sandwich-type prefabricated structure is sintered to finally obtain a C / C-Cu joint.
[0014] Furthermore, the amount ratio of the SiC whisker, AgCuTi powder and binder is (4~6g)g~(0.4~0.6)g:0.50g; The binder is prepared by mixing vaseline and liquid paraffin in a mass ratio of 1:1, heating in an oil bath at a temperature of 75-85 for 30-40 minutes, and then cooling in air to room temperature. The pretreatment includes grinding, cleaning and drying in sequence.
[0015] Furthermore, the process parameters of the sintering treatment are: brazing temperature is 860°C, brazing time is 10 min, furnace vacuum is 6.0×10 -3 Pa-8.0×10 -3 Pa, the heating rate is 6-8℃ / min, and the cooling rate is 4-6℃ / min.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a preparation method of a nanoporous carbon coated SiC whisker modified AgCuTi solder. Firstly, the SiC whisker is subjected to a nanoporous carbon coating treatment, and the nanoporous carbon and AgCuTi are combined to form a composite solder. The space around the SiC whisker subjected to the porous carbon coating treatment is optimized, and the polymorphic nucleation sites dispersed by the porous carbon are in multi-point contact with the solder during the soldering reaction process, so that the brittle Ti-Cu phase around the whisker is intermittently distributed and its growth is inhibited, and finally the effect of refining the brittle phase is achieved. At the same time, the coating of the porous carbon on the whisker surface avoids direct contact between the SiC whisker and the active solder, alleviates the overreaction between the two, reduces the loss degree of the solder on the SiC nano phase, maximizes the mechanical properties of the reinforcement phase, and increases the shear strength of the joint.
[0017] The present invention also discloses the use of the nanoporous carbon coated SiC whisker modified AgCuTi solder prepared by the preparation method in brazing C / C-Cu joints, wherein the pre-coated porous carbon grows upright around the SiC whisker and is distributed in a porous thin layer space structure, and the porous carbon coated SiC whisker and AgCuTi are mixed in a certain proportion to prepare a composite solder; according to relevant experimental results, compared with the untreated AgCuTi composite solder, the strength of the prepared C / C-Cu joint is increased from 31.5MPa to 37.1-53.0MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The microscopic morphology pictures of the nanoporous carbon-coated SiC whiskers prepared in Comparative Example 2, Comparative Example 3 and Example 2 of the present invention and the microscopic morphology picture of the composite solder in Comparative Example 2; Among them: a 1 -a 3 a-microscopic morphology pictures of SiC whiskers, pyrolytic carbon-coated SiC whiskers and nanoporous carbon-coated SiC whiskers used in the composite solders prepared in Comparative Example 2, Comparative Example 3 and Example 2; b-TEM high-magnification picture of porous carbon-coated nanowhiskers prepared in Example 2 of the present invention; c-microscopic morphology picture of the composite solder in Comparative Example 2; Figure 2 The backscattered electron microscopic morphology pictures and partial magnified pictures of the C / C-Cu joints prepared in Example 2 and Example 4 of the present invention; Wherein: a is the overall morphology of the brazing seam of the C / C-Cu joint prepared in Example 2 of the present invention; b is the local enlarged morphology of the middle layer of the brazing seam of the C / C-Cu joint prepared in Example 2 of the present invention; c is the overall morphology of the brazing seam of the C / C-Cu joint prepared in Example 4 of the present invention; d is the local enlarged morphology of the middle layer of the brazing seam of the C / C-Cu joint prepared in Example 4 of the present invention; Figure 3 A bar graph showing the average room temperature shear strength of C / C-Cu joints prepared in Example 1, Example 2, Example 3, and Example 4 of the present invention; Figure 4 The thermal expansion coefficient of the composite solder prepared in Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 varies with temperature; Figure 5 The microscopic morphology pictures of the brazing seams of the C / C-Cu joints prepared in Comparative Examples 1, 2 and 3 of the present invention and the partial enlarged picture of Comparative Example 3; Figure 6 This is a bar chart of the room temperature average shear strength of C / C-Cu joints prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 2 of the present invention. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0024] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0025] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0026] Example 1 A method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder comprises the following steps: Step 1: placing SiC whisker powder in a chemical vapor deposition furnace, using methanol as a precursor, and performing chemical vapor deposition treatment at 1170°C for 4 h to obtain nanoporous carbon-coated SiC whiskers; Step 2: Use an analytical balance to take 0.0125g of nanoporous carbon-coated SiC whiskers and 4.9875g of AgCuTi powder, respectively, and then place them in a 50mL beaker with 30mL of anhydrous ethanol, and stir evenly on a 75°C constant temperature heating magnetic stirrer until the anhydrous ethanol is evaporated, collect the powder and grind it in a mortar for 30min until the powder color is uniform and there is no obvious stratification phenomenon, and finally obtain a nanoporous carbon-coated SiC whisker modified AgCuTi solder with a SiC mass fraction of 0.25wt.%; The obtained nanoporous carbon-coated SiC whisker-modified AgCuTi solder was applied in brazing C / C-Cu joints: Step 3: Add 0.5 g of a homemade binder mixed with liquid paraffin and vaseline in a mass ratio of 1:1 to 5 g of the nanoporous carbon-coated SiC whisker-modified AgCuTi solder, and mix thoroughly to obtain a mixed slurry; Step 4: Cut C / C and Cu into small pieces of 15mm×10mm×4mm, polish the connection surface with 600# sandpaper, place it in anhydrous ethanol for ultrasonic cleaning for 15min, and then place the sample in a drying oven at 65℃ for 1h; Step 5: evenly apply the mixed slurry to the surfaces of C / C and Cu to be connected, and laminate them to form a sandwich-type prefabricated structure; Step 6: Place the sandwich prefabricated structure in a vacuum brazing furnace for sintering. The brazing temperature is 860°C, the brazing time is 10 min, and the furnace vacuum is 6.6×10 -3 Pa, the heating rate was 6℃ / min, and the cooling rate was 4℃ / min, and finally the C / C-Cu joint with an average shear strength of 37.1MPa was obtained.
[0027] Example 2 A method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder comprises the following steps: Step 1: placing SiC whisker powder in a chemical vapor deposition furnace, using methanol as a precursor, and performing chemical vapor deposition treatment at 1170°C for 4 h to obtain nanoporous carbon-coated SiC whiskers; Step 2: Use an analytical balance to take 0.025g of nanoporous carbon-coated SiC whiskers and 4.975g of AgCuTi powder, respectively, and then place them in a 50mL beaker with 30mL of anhydrous ethanol, and stir evenly on a 75°C constant temperature heating magnetic stirrer until the anhydrous ethanol is evaporated, collect the powder and grind it in a mortar for 30min until the powder color is uniform and there is no obvious stratification phenomenon, and finally obtain a nanoporous carbon-coated SiC whisker modified AgCuTi solder with a SiC mass fraction of 0.50wt.%; The obtained nanoporous carbon-coated SiC whisker-modified AgCuTi solder was applied in brazing C / C-Cu joints: Step 3: Add 0.5 g of a homemade binder mixed with liquid paraffin and vaseline in a mass ratio of 1:1 to 5 g of the nanoporous carbon-coated SiC whisker-modified AgCuTi solder, and mix thoroughly to obtain a mixed slurry; Step 4: Cut C / C and Cu into small pieces of 15mm×10mm×4mm, polish the connection surface with 600# sandpaper, place it in anhydrous ethanol for ultrasonic cleaning for 15min, and then place the sample in a drying oven at 65℃ for 1h; Step 5: evenly apply the mixed slurry to the surfaces of C / C and Cu to be connected, and laminate them to form a sandwich-type prefabricated structure; Step 6: Place the sandwich prefabricated structure in a vacuum brazing furnace for sintering. The brazing temperature is 860°C, the brazing time is 10 min, and the furnace vacuum is 6.6×10 -3 Pa, the heating rate was 6℃ / min, and the cooling rate was 4℃ / min, and finally the C / C-Cu joint with an average shear strength of 53.0MPa was obtained.
[0028] Example 3 A method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder comprises the following steps: Step 1: placing SiC whisker powder in a chemical vapor deposition furnace, using methanol as a precursor, and performing chemical vapor deposition treatment at 1170°C for 4 h to obtain nanoporous carbon-coated SiC whiskers; Step 2: Use an analytical balance to take 0.0375g of nanoporous carbon-coated SiC whiskers and 4.9625g of AgCuTi powder, respectively, and then place them in a 50mL beaker with 30mL of anhydrous ethanol, and stir evenly on a 75°C constant temperature heating magnetic stirrer until the anhydrous ethanol is evaporated, collect the powder and grind it in a mortar for 30min until the powder color is uniform and there is no obvious stratification phenomenon, and finally obtain a nanoporous carbon-coated SiC whisker modified AgCuTi solder with a SiC mass fraction of 0.75wt.%; The obtained nanoporous carbon-coated SiC whisker-modified AgCuTi solder was applied in brazing C / C-Cu joints: Step 3: Add 0.5 g of a homemade binder mixed with liquid paraffin and vaseline in a mass ratio of 1:1 to 5 g of the nanoporous carbon-coated SiC whisker-modified AgCuTi solder, and mix thoroughly to obtain a mixed slurry; Step 4: Cut C / C and Cu into small pieces of 15mm×10mm×4mm, polish the connection surface with 600# sandpaper, place it in anhydrous ethanol for ultrasonic cleaning for 15min, and then place the sample in a drying oven at 65℃ for 1h; Step 5: evenly apply the mixed slurry to the surfaces of C / C and Cu to be connected, and laminate them to form a sandwich-type prefabricated structure; Step 6: Place the sandwich prefabricated structure in a vacuum brazing furnace for sintering. The brazing temperature is 860°C, the brazing time is 10 min, and the furnace vacuum is 6.6×10 -3 Pa, the heating rate was 6℃ / min, the cooling rate was 4℃ / min, and finally the C / C-Cu joint with an average shear strength of 47.5MPa was obtained.
[0029] Example 4 A method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder comprises the following steps: Step 1: placing SiC whisker powder in a chemical vapor deposition furnace, using methanol as a precursor, and performing chemical vapor deposition treatment at 1170°C for 4 h to obtain nanoporous carbon-coated SiC whiskers; Step 2: Use an analytical balance to take 0.05 g of nanoporous carbon-coated SiC whiskers and 4.95 g of AgCuTi powder, respectively, and then place them in a 50 mL beaker with 30 mL of anhydrous ethanol, and stir evenly on a 75 ° C constant temperature heating magnetic stirrer until the anhydrous ethanol is evaporated, collect the powder and grind it in a mortar for 30 minutes until the powder color is uniform and there is no obvious stratification phenomenon, and finally obtain a nanoporous carbon-coated SiC whisker modified AgCuTi solder with a SiC mass fraction of 1.0wt.%; The obtained nanoporous carbon-coated SiC whisker-modified AgCuTi solder was applied in brazing C / C-Cu joints: Step 3: Add 0.5% liquid paraffin and vaseline in a mass ratio of 1:1 to 5g of nanoporous carbon-coated SiC whisker-modified AgCuTi solder, and mix thoroughly to obtain a mixed slurry; Step 4: Cut C / C and Cu into small pieces of 15mm×10mm×4mm, polish the connection surface with 600# sandpaper, place it in anhydrous ethanol for ultrasonic cleaning for 15min, and then place the sample in a drying oven at 65℃ for 1h; Step 5: evenly apply the mixed slurry to the surfaces of C / C and Cu to be connected, and laminate them to form a sandwich-type prefabricated structure; Step 6: Place the sandwich prefabricated structure in a vacuum brazing furnace for sintering. The brazing temperature is 860°C, the brazing time is 10 min, and the furnace vacuum is 6.6×10 -3 Pa, the heating rate was 6℃ / min, and the cooling rate was 4℃ / min, and finally the C / C-Cu joint with an average shear strength of 39.4MPa was obtained.
[0030] Example 5 A method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder comprises the following steps: Step 1: placing SiC whisker powder in a chemical vapor deposition furnace, using methanol as a precursor, and performing chemical vapor deposition treatment at 1140° C. for 2 h to obtain nanoporous carbon-coated SiC whiskers; Step 2: Use an analytical balance to take 0.05g of nanoporous carbon-coated SiC whiskers and 4.95g of AgCuTi powder and mix them respectively. Then put them and 50mL of acetone in a 30mL beaker and stir them evenly on a constant temperature heating magnetic stirrer at 85℃ until the anhydrous ethanol is evaporated. Collect the powder and grind it in a mortar for 60min until the powder color is uniform and there is no obvious stratification. Finally, nanoporous carbon-coated SiC whiskers modified AgCuTi solder are obtained.
[0031] Comparative Example 1: Step 1: The pure AgCuTi powder without any treatment is recorded as powder A; Step 2: Add 0.5 g of binder to powder A and mix well to obtain slurry B; Step 3: C / C and Cu were cut into small pieces of 15mm×10mm×4mm, the connection surfaces were polished with 600# sandpaper, and then ultrasonically cleaned in anhydrous ethanol for 15min, and then the samples were placed in a drying oven at 65℃ for 2h to obtain sample C; Step 4: Slurry B is evenly applied to the surfaces of samples C and D, and sample C is assembled into a sandwich-type prefabricated structure to obtain sample E; Step 5: Place E in a vacuum brazing furnace for sintering. The brazing temperature is 860°C, the brazing time is 10 min, and the furnace vacuum is 6.6×10 -3Pa, the heating rate was 6℃ / min, and the cooling rate was 4℃ / min, and finally the C / C-Cu joint with an average shear strength of 31.5 MPa was obtained.
[0032] Comparative Example 2: Step 1: The SiC whiskers without any treatment are recorded as powder A; Step 2: Add 0.5% by mass of powder A to pure AgCuTi powder to obtain powder B; Step 3: Powder B is placed in anhydrous ethanol and stirred evenly on a constant temperature heated magnetic stirrer until the anhydrous ethanol is evaporated to dryness, and then the powder is ground in a mortar for 40 minutes until the powder color is uniform and there is no obvious stratification phenomenon, and 0.5 g of a binder is added thereto, and slurry C is obtained after mixing evenly; Step 4: C / C and Cu were cut into small pieces of 15mm×10mm×4mm, the connection surfaces were polished with 600# sandpaper, and then ultrasonically cleaned in anhydrous ethanol for 15min. The samples were then placed in a drying oven at 65℃ for 1h to obtain samples D and E. Step 5: Evenly apply slurry C to the surfaces of samples D and E, and assemble C, D, and E into a sandwich-type prefabricated structure to obtain sample F; Step 6: Place F in a vacuum brazing furnace for sintering. The brazing temperature is 860°C, the brazing time is 10 min, and the furnace vacuum is 6.6×10 -3 Pa, the heating rate was 6℃ / min, and the cooling rate was 4℃ / min, and finally the C / C-Cu joint with an average shear strength of 43.3 MPa was obtained.
[0033] Comparative Example 3: Step 1: placing SiC whiskers in a chemical vapor deposition furnace, using methane as a precursor, and depositing at 1070° C. for 10 min to obtain powder A having a pyrolytic carbon layer coating thickness similar to that of the nanoporous carbon coating in Example 1-4; Step 2: Use an analytical balance to mix 0.025g of powder A and 4.975g of AgCuTi powder to obtain 5g of composite solder with 0.5wt% SiC, which is recorded as powder B; Step 3: Powder B is placed in anhydrous ethanol and stirred evenly on a constant temperature heated magnetic stirrer until the anhydrous ethanol is evaporated to dryness, and then the powder is ground in a mortar for 40 minutes until the powder color is uniform and there is no obvious stratification phenomenon, and 0.5 g of a binder is added thereto, and slurry C is obtained after mixing evenly; Step 4: C / C and Cu were cut into small pieces of 15mm×10mm×4mm, the connection surfaces were polished with 600# sandpaper, and then ultrasonically cleaned in anhydrous ethanol for 15min. The samples were then placed in a drying oven at 65℃ for 1h to obtain samples D and E. Step 5: Evenly apply slurry C to the surfaces of samples D and E, and assemble C, D, and E into a sandwich-type prefabricated structure to obtain sample F; Step 6: Place F in a vacuum brazing furnace for sintering. The brazing temperature is 860°C, the brazing time is 10 min, and the furnace vacuum is 6.6×10 -3 Pa, the heating rate was 6℃ / min, and the cooling rate was 4℃ / min, and finally the C / C-Cu joint with an average shear strength of 36.7 MPa was obtained.
[0034] Figure 1 The microscopic morphology pictures of the nanoporous carbon-coated SiC whiskers prepared in Comparative Example 2, Comparative Example 3 and Example 2 of the present invention and the microscopic morphology picture of the composite solder in Comparative Example 2 show that the nanocarbon layer successfully wraps the SiC whiskers, and the SiC whiskers and AgCuTi metallurgical powder in the composite solder are evenly mixed, indicating that the introduced content of the whiskers is appropriate.
[0035] Figure 2 The backscattered electron microscopic morphology pictures and partial magnified pictures of the C / C-Cu joints prepared in Example 2 and Example 4 of the present invention show that when the mass fraction of the porous carbon-coated SiC whiskers is 0.5wt%, due to the introduction of appropriate whiskers and porous carbon, small-sized Ti-Cu grains are intermittently distributed along the edges of the residual whiskers, and the Ag and Cu solid solutions are evenly distributed throughout the brazing layer, and the overall organizational morphology of the brazing layer is refined. When the mass fraction of the porous carbon-coated SiC is 1.0wt.%, excess whiskers are prone to agglomeration, resulting in the destruction of the Ag matrix, and defects of varying degrees appear in the intermediate layer and the reaction layer. In addition, the aggregation of the Ti-Cu phase occurs in areas with fewer whiskers.
[0036] Figure 3 The bar chart shows the average strength of C / C-Cu joints prepared in Example 1, Example 2, Example 3 and Example 4 of the present invention. It can be seen from the figure that the mechanical properties of the composite solder brazing joint under the porous carbon-coated SiC content corresponding to Example 2 are the best, which is 53.0 MPa.
[0037] Figure 4The thermal expansion coefficient of the composite solder prepared in Example 2 of the present invention and Comparative Examples 1, 2, and 3 varies with temperature. It can be seen that after adding SiC whiskers, the thermal expansion coefficient of the AgCuTi solder decreases, especially after the temperature rises. This reduces the difference in thermal expansion coefficient between it and the base material, which is beneficial to relieve the residual thermal stress at the joint.
[0038] Figure 5 The microscopic morphology pictures of C / C-Cu joints prepared by Comparative Examples 1, 2 and 3 of the present invention and the partial enlarged picture of Comparative Example 3 show that when brazing with the composite brazing material composed of SiC whiskers without coating treatment, the whisker phase agglomerates in the center of the brazing layer and cannot act on the entire brazing layer. When brazing with the composite brazing material composed of SiC whiskers coated with pyrolytic carbon, due to the lack of pore structure and fewer active sites for reaction, TiC brittle particles will gather around the whisker phase, which has a very limited effect on the spatial distribution of the Ti-Cu phase, and the size of the brittle Ti-Cu phase is significantly increased, which has limited improvement in the mechanical properties of the joint.
[0039] Figure 6 The bar graphs are the average strengths of C / C-Cu joints prepared in Comparative Examples 1, 2, 3 and Example 2 of the present invention. It can be seen from the graphs that the shear resistance of all C / C-Cu joints brazed with composite solders with SiC whiskers added is improved compared with that of joints brazed with pure AgCuTi solder. Among them, the joint brazed with composite solder prepared with spatial porous carbon coated SiC whiskers has the best mechanical properties.
[0040] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder, characterized in that: The following steps are involved: The SiC whiskers are subjected to chemical vapor deposition treatment to obtain nanoporous carbon-coated SiC whiskers; The nanoporous carbon-coated SiC whisker and AgCuTi powder are mixed and added into a solvent for stirring. The powder is collected and ground to obtain the nanoporous carbon-coated SiC whisker modified AgCuTi solder.
2. The method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder according to claim 1, characterized in that: The chemical vapor deposition process uses methanol as a precursor and deposits at 1140-1170° C. for 2-4 hours.
3. The method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder according to claim 1, characterized in that: The dosage ratio of the nanoporous carbon-coated SiC whisker, AgCuTi powder and solvent is (0.0125 g-0.05) g: (4.9875-4.975) g: 30 mL.
4. The method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder according to claim 1, characterized in that: The solvent is ethanol; The stirring is magnetic stirring; the temperature of the magnetic stirring is 75-85°C.
5. The method for preparing a nanoporous carbon-coated SiC whisker-modified AgCuTi solder according to claim 1, characterized in that: The grinding time is 30 to 60 minutes.
6. A nanoporous carbon-coated SiC whisker modified AgCuTi solder, characterized in that: The method is prepared by any one of claims 1 to 5.
7. The use of a nanoporous carbon-coated SiC whisker modified AgCuTi solder according to claim 6, characterized in that: The invention discloses an application of the nanoporous carbon coated SiC whisker modified AgCuTi solder in brazing C / C-Cu joints.
8. The use of a nanoporous carbon-coated SiC whisker modified AgCuTi solder according to claim 7, characterized in that: When the nanoporous carbon-coated SiC whisker-modified AgCuTi solder is used in brazing a C / C-Cu joint, the method comprises the following steps: The nanoporous carbon-coated SiC whisker-modified AgCuTi solder and a binder are mixed to obtain a mixed slurry; The C / C and Cu are pretreated, and then the mixed slurry is applied to the surfaces of the C / C and Cu to be connected, and then they are bonded to form a sandwich-type prefabricated structure; The obtained sandwich-type prefabricated structure is sintered to finally obtain a C / C-Cu joint.
9. The use of a nanoporous carbon-coated SiC whisker modified AgCuTi solder according to claim 8, characterized in that: The amount ratio of the SiC whisker, AgCuTi powder and binder is (4-6g)g-(0.4-0.6)g:0.50g; The binder is prepared by mixing vaseline and liquid paraffin in a mass ratio of 1:1, heating in an oil bath at a temperature of 75-85°C for 30-40 minutes, and then cooling in air to room temperature. The pretreatment includes grinding, cleaning and drying in sequence.
10. The use of a nanoporous carbon-coated SiC whisker modified AgCuTi solder according to claim 8, characterized in that: The process parameters of the sintering treatment are: brazing temperature is 860°C, brazing time is 10 min, furnace vacuum is 6.0×10 -3 Pa-8.0×10 -3 Pa, the heating rate is 6-8℃ / min, and the cooling rate is 4-6℃ / min.
Citation Information
Patent Citations
Micro-nano powder modified active brazing filler metal and preparation method thereof
CN112222676A
Copper-plated carbon nanotube reinforced Ag-Cu-Ti composite brazing filler metal and preparation method thereof
CN114589432A
Surface modified granular reinforcement copper-based composite material used for spot-welding electrode
CN1947922A
Adjustment of surface of substrate and method therefor
JP1995258865A
Laser Guided Nano-Brazing Method for Reinforced Aluminum Composite Material having High Volume Fraction Silicon Carbide Particles
US20150196965A1